2003
DOI: 10.1046/j.1365-2559.2003.01622.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological associations of CD44 mRNA and protein expression in primary breast carcinomas

Abstract: Quantitative real-time RT-PCR revealed clinical correlations of CD44s and CD44v6 mRNA expression in breast carcinomas while immunohistochemistry for the protein expression of CD44s and other CD44 variants did not. This contradictory result merits further studies concerning the clinical impact of CD44 molecules in breast carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 59 publications
2
21
0
Order By: Relevance
“…Our results confirm a recent smaller study of CD44s mRNA expression in invasive breast carcinoma by Berner et al, who reported a significant correlation between CD44s mRNA expression by reverse transcription-PCR analysis and both disease-free and overall survival (17). Our results suggest that CD44s protein expression (or expression of a variant recognized with the anti-CD44s antibody) may be a favorable prognostic factor in node-negative invasive breast carcinoma.…”
Section: Discussionsupporting
confidence: 91%
“…Our results confirm a recent smaller study of CD44s mRNA expression in invasive breast carcinoma by Berner et al, who reported a significant correlation between CD44s mRNA expression by reverse transcription-PCR analysis and both disease-free and overall survival (17). Our results suggest that CD44s protein expression (or expression of a variant recognized with the anti-CD44s antibody) may be a favorable prognostic factor in node-negative invasive breast carcinoma.…”
Section: Discussionsupporting
confidence: 91%
“…These studies are summarized in Table 1, which notes the tumor grade examined (e.g., benign or invasive) and the CD44 isoforms examined when that information was provided by the authors. Of interest, 8 out of 10 studies that focused on mammary tumors classified as either noninvasive or lymph node-negative showed that CD44s (and in some cases CD44v6) expression correlates with favorable prognosis or cellular differentiation, indicative of antitumoral activity (91,(93)(94)(95)(96)(97)(98)(99). The exception to this is a 1995 study by Kaufmann and colleagues (64), who examined tumors graded as node-negative and reported that CD44v6 expression correlates with poor OS.…”
Section: Histopathological Cd44 In Human Cancermentioning
confidence: 99%
“…Unlike hyaluronan, increased expression of CD44s correlates with overall patient survival (40,41). Furthermore, CD44s is expressed at a higher level in tubular carcinoma, a subtype of breast ductal carcinoma that rarely metastasize, compared with invasive micropapillary carcinoma, a variant of breast ductal carcinoma with a high metastatic potential and poor clinical outcome (42).…”
Section: Roles Of Hyaluronan and Cd44 In Breast Cancermentioning
confidence: 99%